REST AREA DI PULAU TAYAN - Tjianto, Fendy; Zain, Zairin; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
One of facilities that should be on high road is rest area. According to Department of Common work the distance between rest area should be more than 4 km but less than 30 km. Trans Borneo Road which is connect West Borneo Province and Mid Borneo Province has length around 1.285 km. Consider from the length, Trans Borneo Road should be have several rest areas. Pak Kasih Bridge is the bridge that connect Trans Borneo Road across Kapuas River and Tayan Island which is located on KM 121 of Trans Kalimantan Road (measure from Pontianak City). Consider from the distance between Tayan Island and Pontianak City nor Palangkaraya City appropriate to rule of distance between rest area, then Tayan Island is the great place for rest area. The design begins with an analysis of the subjects and human behavior or vehicles that passing through on Tayan Island. Analyses were also conducted on the existing of Tayan Island. The results were obtained two different zoning area which is each of zoning have the functions of the building to accommodate human activity. Emphasis of circulation is done by combining the functions of different buildings, and also different zoning. The results of the design are the rest area with the incorporation of multi-functional building with an emphasis on circulation.